Ahli Waris ‘Ashabah Perspektif Hukum Keluarga Islam - Arofik, Slamet; Fidaroini, Rafida (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2021)
Among the heirs who get the inheritance of the deceased are the heirs of 'ashabah. These heirs are "legally formal" their existence is mentioned in the texts from both the Qur'an and al-Hadith. However, the text does not mention literally the portion that will be obtained by this heir. As the name bears, they are the recipients of the remaining inheritance after the inheritance is distributed to ashab al-furudl. Therefore, they sometimes get more and sometimes get less. Even in certain circumstances the heirs of 'ashabah may not get a share of the inheritance at all.